A Novel circUBR4/miR-491-5p/NRP2 ceRNA Network Regulates Oxidized Low-density Lipoprotein-induced Proliferation and Migration in Vascular Smooth Muscle Cells. Issue 4 (April 2022) - Peng, Huaiyu; Liu, Shunfan; Li, Yi; Wang, Chengyang; Zhong, Yongjin
Abstract : Supplemental Digital Content is Available in the Text. Abstract: Vascular smooth muscle cells (VSMCs) play critical roles in the progression of atherosclerosis. Circular RNA (circRNA) ubiquitin protein ligase E3 component n-recognin 4 (circUBR4) has been shown to regulate VSMC migration and proliferation. In this study, we sought to identify the mechanism in the regulation of circUBR4. CircUBR4, microRNA (miR)-491-5p, and Neuropilin-2 (NRP2) were quantified by quantitative real-time polymerase chain reaction (PCR) and western blot. Cell proliferation was evaluated by Cell Counting Kit-8 and 5-Ethynyl-2′-Deoxyuridine assays. Cell migration was examined by wound-healing and transwell invasion assays. The direct relationship between miR-491-5p and circUBR4 or NRP2 was validated by dual-luciferase reporter and RNA immunoprecipitation assays. Our data indicated that in VSMCs, ox-LDL induced circUBR4 expression. Silencing endogenous circUBR4 attenuated VSMC proliferation and migration induced by ox-LDL. Mechanistically, circUBR4 targeted miR-491-5p by pairing to miR-491-5p. Moreover, miR-491-5p was identified as a downstream mediator of circUBR4 function in ox-LDL–treated VSMCs. NRP2 was a direct target of miR-491-5p, and circUBR4 acted as a competing endogenous RNA for miR-491-5p to regulate NRP2 expression. In addition, NRP2 was a functionally downstream effector of miR-491-5p in regulating ox-LDL–evoked VSMC proliferation and migration. Our findings identify a new competing endogenous RNA network, the circUBR4/miR-491-5p/NRP2 axis, for the regulation of circUBR4 in VSMC migration and proliferation.